Bacterial toxin's DNA vaccine serves as a strategy for the treatment of cancer, infectious and autoimmune diseases. (November 2016) - Behzadi, Elham; Halabian, Raheleh; Hosseini, Hamideh Mahmoodzadeh; Fooladi, Abbas Ali Imani
Abstract: DNA vaccination –a third generation vaccine-is a modern approach to stimulate humoral and cellular responses against different diseases such as infectious diseases, cancer and autoimmunity. These vaccines are composed of a gene that encodes sequences of a desired protein under control of a proper (eukaryotic or viral) promoter. Immune response following DNA vaccination is influenced by the route and the dose of injection. In addition, antigen presentation following DNA administration has three different mechanisms including antigen presentation by transfected myocytes, transfection of professional antigen presenting cells (APCs) and cross priming. Recently, it has been shown that bacterial toxins and their components can stimulate and enhance immune responses in experimental models. A study demonstrated that DNA fusion vaccine encoding the first domain (DOM) of the Fragment C (FrC) of tetanus neurotoxin (CTN) coupled with tumor antigen sequences is highly immunogenic against colon carcinoma. DNA toxin vaccines against infectious and autoimmune diseases are less studied until now. All in all, this novel approach has shown encouraging results in animal models, but it has to go through adequate clinical trials to ensure its effectiveness in human. However, it has been proven that these vaccines are safe, multifaceted and simple and can be used widely in organisms which may be of advantage to public health in the near future. This paper outlines the mechanism of the action of DNA vaccines and their possible application for targeting infectious diseases, cancer and autoimmunity. Highlights: DNA toxin vaccine and bacterial toxin. DNA toxin vaccine as a treatment option. Bacterial toxin's DNA vaccine for immune therapy.